1983
DOI: 10.1021/ja00359a030
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between thiophene hydrodesulfurization activity and the number of first sulfur neighbors as determined by EXAFS in sulfided .gamma.-alumina-supported cobalt-molybdenum (CoMo/.gamma.-Al2O3) samples

Abstract: 12) In agreement with this hypothesis, attempts to prepare the parent complex CpRe(CO)2CH2CH2CH2 from 1,3-diiodopropane and 1,3-propaneditosylate have yielded only cyclopropane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Therefore, MoS 2 species forming on these catalysts had a smaller basal plane size as suggested in previous studies (Koizumi, Yamazaki, Hatanaka & Yamada, 1997;Yamada et al, 1999;Bouwens et al, 1990;Fujikawa et al, 2006;Nicosia & Prins, 2005). The coordination number of the Mo-S and Mo-Mo shells increased slightly with the Ni : Mo ratio, suggesting that the crystallinity of the MoS 2 species improved by the addition of the Ni (Co) promoter (Kasahara et al, 1994;Boudart et al, 1983). It is also noted that the quality of fitting hardly improved by the addition of the Mo-Ni coordination shell in the fitting analysis.…”
Section: Effect Of the Ni : Mo Molar Ratio On Mo K-edgesupporting
confidence: 52%
“…Therefore, MoS 2 species forming on these catalysts had a smaller basal plane size as suggested in previous studies (Koizumi, Yamazaki, Hatanaka & Yamada, 1997;Yamada et al, 1999;Bouwens et al, 1990;Fujikawa et al, 2006;Nicosia & Prins, 2005). The coordination number of the Mo-S and Mo-Mo shells increased slightly with the Ni : Mo ratio, suggesting that the crystallinity of the MoS 2 species improved by the addition of the Ni (Co) promoter (Kasahara et al, 1994;Boudart et al, 1983). It is also noted that the quality of fitting hardly improved by the addition of the Mo-Ni coordination shell in the fitting analysis.…”
Section: Effect Of the Ni : Mo Molar Ratio On Mo K-edgesupporting
confidence: 52%
“…Silbernagel et al showed that HDS activity correlated with Mo5+ defects ion MoS2.33 Boudart et al found that HDS activity was maximized when the metal atoms were deficient one sulfur atom in their nearest-neighbor shell. 34 The importance of Lewis surface acidity was suggested by Hou and Wise, who showed that HDS activity correlated with NH3 adsorption. 35 In addition, several investigators have observed that pyridine, a Lewis base, poisons desulfurization of thiophene.…”
Section: Discussionmentioning
confidence: 97%
“…The solvent was then removed in vacuo and the residue was separated by TLC on silica gel using 1:1 hexane/CH 2 Cl 2 solvent mixture to yield in order of elution 7.5 mg (41%) of brown-green CpFeMn 2 (CO) 7 (l 3 -S 2 ) 2 (2) and 1.1 mg (5%) of Cp 3 Fe 3 Mn(CO) 4 (l 3 -S 2 ) 2 (l 3 -S) (3). The known compound [CpFe(CO) 2 ] 2 can subsequently be eluted from the baseline in approx.…”
Section: Reaction Of [Cpfemn(co) 5 (L 3 -S 2 )] 2 (1) With Comentioning
confidence: 99%
“…Polynuclear metal-sulfur complexes exhibit a range of different structural types [2]. Mixed-metal sulfido cluster complexes have attracted attention because of possible synergistic effects [3] exhibited by certain types of heterogeneous metal sulfide catalysts [4].…”
Section: Introductionmentioning
confidence: 99%